Examining Some of Students’ Views on the Nature of Science (NOS) in Traditional Lecture Format Teaching Environment - Issa I. Salame; Shirley Dong (Universitas Islam Indonesia, 2021)
The preparation of a scientifically literate society is the main goal of science education throughout the world and this has resulted in the emphasis of nature of science in the curriculum. The purpose of this research project is to examine the aforementioned students’ views on NOS tenets, its relationship to their academic achievements and background, and how it changes through their study of science. The study took place at the City College of New York, an urban, commuter, public college, and minority serving institute. The research data was collected through the administration of a survey that contained three of the NOS questions and academic and background information about the students. The data suggest that students possess inadequate understanding of the nature of science when they begin their academic fields of science study. This inadequate understanding is resistant to change in traditional science teaching settings. The data provide evidence that the inadequate understanding of nature of science does not change as the result of exposure to science courses, the field of science studied, and the students’ academic achievement as measured by grade point average. Our data show that traditional instruction in college science courses does not address nature of science and does not cause a conceptual change in the students’ understanding of NOS. The lack of correlation between students’ understanding of nature of science and credits completed or grade point average could be attributed to students relying on rote-learning and algorithmic problem-solving to achieve high grades and succeed in science, which hinders their meaningful learning of science and the development of conceptual understanding. Thus, science teaching and instruction should address naïve conception on the NOS and changes the instruction methods to consider NOS naïve conceptions and learning challenges. Science teaching and learning curriculum and instruction should immerse students in science learning activities that nurtures their understanding of the nature of science through participating in novel science research and inquiry-based learning activities.